2007
DOI: 10.1111/j.1600-0897.2006.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative Predictors of Antibodies Against Follicle‐Stimulating Hormone in Female Infertility: A Study Based on In Vitro Fertilization Patients

Abstract: Anti-FSH may be naturally occurring antibodies associated with peripheral FSH concentrations, but increased in infertile women with dysregulation of immune reactions and repeatedly performed IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 31 publications
2
39
0
2
Order By: Relevance
“…The levels of anti‐FSH IgM antibodies were associated with peripheral FSH levels on patients with tubal and male factor infertility 17. According to these authors, the anti‐FSH IgA antibodies detected in serum could be part of the mucosal response involved in the induction of immune tolerance to seminal constituents,18 as FSH is also present in semen.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The levels of anti‐FSH IgM antibodies were associated with peripheral FSH levels on patients with tubal and male factor infertility 17. According to these authors, the anti‐FSH IgA antibodies detected in serum could be part of the mucosal response involved in the induction of immune tolerance to seminal constituents,18 as FSH is also present in semen.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown the presence of anti‐FSH antibodies (IgG, IgM and IgA) on healthy non‐pregnant women and a decrease in IgG and IgM on uncomplicated pregnancy 15 and an increase in those antibodies on infertile women 15, 16. The levels of anti‐FSH IgM antibodies were associated with peripheral FSH levels on patients with tubal and male factor infertility 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain data indicate reduced estrogen receptor (ER) expression in females with unexplained infertility (2). ERs are nuclear hormone receptors activated by estradiol, a critical reproductive hormone (3).…”
Section: Introductionmentioning
confidence: 99%
“…Una de las posibles causas de esta disminución de la respuesta podría ser la generación de anticuerpos frente a las hormonas administradas, como es el caso de eCG, incluso administrada en bajas dosis Swanson et al, 1996;. Esto explicaría el aumento de la tasa de anticuerpos anti-FSH descrito en mujeres con problemas de infertilidad (Haller et al, 2007) y una relación entre el aumento de anticuerpos anti-FSH en sangre y un aumento de la FSH circulante en sangre (Haller et al, 2007). Además, mientras un mayor número de tratamientos provocaría una mayor respuesta inmunitaria , la alternancia de tratamientos con distintas hormonas (Maurer et al, 1968; o el incremento de los tiempos entre diferentes tratamientos (Maertens and Luzi, 1995;Swanson et al, 1996; podrían reducir el impacto de la repetición de los mismos.…”
Section: Repetición De Tratamientos De Superovulación Sobre Una Mismaunclassified